Impact of an artificial structure on the benthic community composition in the southern North Sea: assessed by a morphological and molecular approach. (12th September 2018) - Klunder, Lise; Lavaleye, Marc S S; Filippidi, Amalia; van Bleijswijk, Judith D L; Reichart, Gert-Jan; van der Veer, Henk W; Duineveld, Gerard C A; Mienis, Furu
Abstract: Man-made structures in the North Sea are known to act as artificial reefs by providing a habitat for sessile epifauna in a predominantly soft sediment environment. This epifauna is hypothesized to cast a so-called "shadow" over the soft sediment ecosystem by altering the nutrient composition in the overlying water column. In addition, the structure itself could alter currents and thereby influence the deposition and erosion of the sediments in the wake of the platform. This study aims to assess the long-term effects of a gas platform in the southern North Sea on the surrounding benthic community by both morphological and molecular identification of benthic species. The species composition and a set of abiotic factors of the sediment around a gas platform were assessed along four transects. Differences for the abiotic factors were found in the closer vicinity of the platform in the direction corresponding to the predominant currents. The number of benthic fauna families found in the molecular approach were on average three times higher than for the morphological approach. Both approaches showed that small differences occurred primarily due to changes in sedimentary organic matter content. Differences in species composition were more pronounced between transects rather than between distances from the platform.